The Effect of Using the Mind Mapping Model on Student Learning Creativity in Science Subjects in Class IV Students at SD Inpres 2 Paranggi - Nuriani, Riska Arifka; B.M Gagaramusu, Yusdin; Satria Dewi Pendit, Sinta; N. Kaharu, Sarintan (Journal of Asian Primary Education (JoAPE), 2024)
The aim of this research is to describe the effect of using the Mind Mapping model on student learning creativity in science subjects for fourth grade students at SD Inpres 2 Paranggi. The population in this study were all fourth grade students at SD Inpres 2 Paranggi, and a sample of 22 respondents was obtained. The data collection technique in this research uses a questionnaire. Partial hypothesis testing (T test) is carried out to analyze the partial influence of the independent variable on the dependent variable. The way to test the T test is to compare the calculated T with the T table at the real level α = 0.05. The T test has a significant effect if the calculation result of T ≥ T table or sig value < 0.05. Ho has influence and Ha has no influence.